Is There a Balance Problem in Hypermobile Patients with Fibromyalgia? - Yasemin ULUS; Yeşim AKYOL; Berna TANDER; Dilek DURMUŞ; Ayhan BİLGİCİ and Ömer KURU (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate the relationship between hypermobility and balance problem and the possible effect of this relationship on fall frequency in patients with fibromyalgia syndrome (FMS). Patients and methods: Sixty female patients with FMS and 30 healthy female controls were included in the study. The mean age of all participants was 41.8±9.9 years with a range of 22 to 62 years. The patients were divided into three groups: group 1 included FMS patients with hypermobility, group 2 included FMS patients without hypermobility, and group 3 included controls. Outcome measures for the FMS patients included disease duration, pain as assessed by the Visual Analog Scale (VAS), disease activity as assessed by the Fibromyalgia Impact Questionnaire (FIQ). The number of falls, functional performance as assessed by six-minute walk distance (6MWD) test, balance as assessed by the one-legged balance test with open eyes in conjunction with the Berg Balance Scale (BBS), and hypermobility as assessed by the Beighton criteria were evaluated in all participants. Results: There was no statistically significant difference between groups 1 and 2 in terms of duration of disease, VAS pain, FIQ, or number of falls (p>0.05). The number of falls was significantly different in group 1 than group 3 (p<0.05). There was no significant difference among the groups in the 6MWD test (p>0.05). The mean one-leg balance testing time and the mean BBS score were significantly different in the three groups (p<0.05). No significant correlation was found among the pain and balance tests and the number of falls (p>0.05). Hypermobility had a significant effect on the balance tests (p<0.001). Conclusion: The balance problem was found to be significantly higher in FMS patients with hypermobility than in those without hypermobility and in the healthy controls. This situation needs to be considered when clinically assessing FMS patients, as well as the patients should be informed, and appropriate measurements should be performed.